Analisis Implementasi Program CSR dan Keberlanjutan PT Pertamina terhadap Lingkungan dan Komunitas Lokal Indonesia (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study analyzes the implementation of PT Pertamina's Corporate Social Responsibility (CSR) program in supporting environmental sustainability and empowering local communities in Indonesia. With the global challenges of climate change and energy transition, companies are expected to focus not only on economic benefits, but also on social and environmental aspects. The purpose of this study is to evaluate the effectiveness of Pertamina's CSR program in reducing negative impacts on the environment and improving the quality of life of local communities. This study uses a qualitative approach with a comparative analysis of the company's sustainability report and related literature studies. The findings show that although Pertamina has recorded several achievements in reducing emissions and conserving ecosystems, there are gaps in program implementation, especially in terms of active involvement of local communities. CSR programs are often top-down, with little active community involvement in planning and evaluation. The implication of this study is the need for a more participatory and collaboration-based CSR approach, in order to produce more sustainable social and environmental impacts.